Stability Study of mRNA-Lipid Nanoparticles Exposed to Various Conditions Based on the Evaluation between Physicochemical Properties and Their Relation with Protein Expression Ability - Mariko Kamiya; Makoto Matsumoto; Kazuma Yamashita; Tatsunori Izumi; Maho Kawaguchi; Shusaku Mizukami; Masako Tsurumaru; Hidefumi Mukai; Shigeru Kawakami (MDPI AG, 2022)
Lipid nanoparticles (LNPs) are currently in the spotlight as delivery systems for mRNA therapeutics and have been used in the Pfizer/BioNTech and Moderna COVID-19 vaccines. mRNA-LNP formulations have been indicated to require strict control, including maintenance at fairly low temperatures during their transport and storage. Since it is a new pharmaceutical modality, there is a lack of information on the systematic investigation of how storage and handling conditions affect the physicochemical properties of mRNA-LNPs and their protein expression ability. In this study, using the mRNA-LNPs with standard composition, we evaluated the effects of temperature, cryoprotectants, vibration, light exposure, and syringe aspiration from the vials on the physicochemical properties of nanoparticles in relation to their in vitro/in vivo protein expression ability. Among these factors, storage at −80 °C without a cryoprotectant caused a decrease in protein expression, which may be attributed to particle aggregation. Exposure to vibration and light also caused similar changes under certain conditions. Exposure to these factors can occur during laboratory and hospital handling. It is essential to have sufficient knowledge of the stability of mRNA-LNPs in terms of their physical properties and protein expression ability at an early stage to ensure reproducible research and development and medical care.